The Influence of Nutrition Education Through The Media Pocketbook on Increasing Knowledge about Healthy Snacks in State Elementary School - Arnisam,; Rasmawati,; Masyudi,; Yuliani Safmila , (Jurnal Serambi Ilmu, 2024)
Research objective: to determine the effect of nutrition education through pocket books on increasing children's knowledge about healthy snacks at SD Negeri 25 "Manulife" Banda Aceh. Methods: This type of research is a quantitative study using a quasi-experimental research design with a pretest-posttest design with a control group design. There were 37 subjects, taking samples with total sampling. This research was conducted on June 20 2022 at SD Negeri 25 "Manulife" Banda Aceh. Results: There was an increase in children's knowledge about healthy snacks before being given nutrition education through the pocket book media of 71.90 and after 88.33 with an increase in knowledge of 16.43 while an increase in children's knowledge about healthy snacks before being given nutrition education without using the media was 77. 56 and after 89.81 with an increase in knowledge of 12.250. Conclusion: There is an effect of providing education on the level of children's knowledge about healthy snacks before and after being given nutrition education with a P-value of 0.003 and without using media with a P-value of 0.005.